Implementation of innovative technologies into lighthouses construction - Sandurska, O. V. (History of science and technology, 2017)
The author emphasizes the need of improving lighthouses construction and conditions of their operation to provide appropriate conditions for trouble-free navigation. Also, in this article the author considers key innovations in lighthouses construction which are connected to power-efficiency requirements. One more important aspect of lighthouses modernization is also fitting lighthouses with modern supervisory control systems and modern electronic equipment.